Artificial neural networks to evaluate the boron concentration decreasing profile in Blood-BPA samples of BNCT patients - Garcia Reiriz, Alejandro Gabriel (2011)
For the prediction of decay concentration profiles of the p-boronophenylalanine (BPA) in blood during BNCT treatment, a method is suggested based on Kohonen neural networks. The results of a model trained with the concentration profiles from the literature are described. The prediction of the model was validated by the leave-one-out method. Its robustness shows that it is mostly independent on small variations. The ability to fit retrospective experimental data shows an uncertainty lower than the two compartment model used previously.